La VAE à l'Université française : entre savoirs et "expérience" - Françoise Ropé (Les éditions de la Maison des sciences de l'Homme, 2005)
In France, since 2002, University degrees may be obtained through validation of personal and professional experiences, without formal education or vocational training. Work-based and personal experience can therefore be validated just as the knowledge transmitted by the university is. The personnel in charge of granting equivalences, plays a key role in assisting applicants to prepare their application. In doing so, they contribute to redefining the notion of experience and its relation to certificates, skills and knowledge.